Increased antipsychotic drug concentration in hospitalized patients with mental disorders following COVID-19 infection: a call for attention - Yang, Rui; Wan, Jin-Ling; Pi, Chen-Qi; Wang, Tian-Hui; Zhu, Xue-Quan; Zhou, Shuang-Jiang (Frontiers in Psychiatry, 2024)
Purpose: Examine the alterations in antipsychotic concentrations following coronavirus disease-2019 (COVID-19) infection among hospitalized patients with mental disorders and conduct an analysis of the factors influencing these changes. Methods: Data were collected from inpatients at Beijing Huilongguan Hospital between December 12, 2022, and January 11, 2023, pre- and post-COVID-19. Based on the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, 329 inpatients with mental disorders were included (3 with incomplete data excluded). Primary outcomes assessed changes in antipsychotic concentrations pre- and post-COVID-19, while secondary outcomes examined factors linked to concentration increases and antipsychotic dose adjustments. Results: Clozapine (P < 0.001), aripiprazole (P < 0.001), quetiapine (P = 0.005), olanzapine (P < 0.001), risperidone (P < 0.001), and paliperidone (P < 0.001) concentrations increased post-COVID-19 in patients with mental disorders. Notably, clozapine concentration surpassing pre-infection levels was highest. Clozapine users were more likely to adjust their dose (50.4%) compared to olanzapine (17.5%) and other antipsychotics. Moreover, traditional Chinese patent medicines and antibiotics during COVID-19 infection were associated with antipsychotic reduction or withdrawal (OR = 2.06, P = 0.0247; OR = 7.53, P = 0.0024, respectively). Conclusion: Antipsychotic concentrations in hospitalized patients with mental disorders increased after COVID-19 infection, that may be related not only to COVID-19, but also to the use of Chinese patent medicines during infection. The pre-infection concentration and types of antipsychotics, patient's gender, and combination of traditional Chinese medicine or antibiotics, were factors found to correlate with increased drug concentrations and necessitate dose adjustments.